Mindfulness for teenagers students: designing an effective Islamic digital therapeutics through adult insights - Mahmud, Murni; Samsuri, Suhaila; Alias, Intan Aidura; Abdul Hamid, Siti Suhaila; Zannat, Nahreen (2025)
This study explored the development of an Islamic digital therapeutic application designed to enhance mindfulness and mental well-being among Muslim student teenagers from adult’s perspective. Acknowledging the critical role of mindfulness in adolescent mental health, this study addressed the significant gap in digital mental health support for these users. This study aimed to identify key Islamic design elements and mindfulness practices suitable for digital adaptation, develop a prototype application, and evaluate its impact on Muslim teenagers' mental well-being. Additionally, this research conducted an extensive investigation into the development of an innovative Islamic digital therapeutic application with the goal of enhancing mindfulness and overall mental well-being among Muslim teenage students. It was determined through this study that mindfulness plays a crucial role in the mental health of adolescents, and there is a substantial lack of digital mental health resources specifically tailored to this demographic. To bridge this gap, the research aimed to identify the essential Islamic design components and mindfulness practices that are suitable for adaptation into a digital therapeutic platform (DTx). Subsequently, a prototypical app was created, based on adults’ perceptions on impact of the mental well-being of Muslim teenagers was assessed. The methodology employed in this research comprised a combination of quantitative methods for content development, user interface design founded on Islamic art principles. The perspectives of adults, including mental health professionals and parents, were crucial in informing both the design and content of the app to ensure its effectiveness and authenticity. This comprehensive approach resulted in the successful development of prototype mobile app appropriately named "Islamic Mindfulness for Teens." The app seamlessly integrates evidence-based psychological interventions with Islamic principles and design elements. The outcomes of this evaluation have far-reaching implications for the advancement of inclusive digital therapeutic solutions and the integration of religious facets into mental health interventions specifically targeting youth populations. The research paper explores the efficacy and acceptance of "Islamic Mindfulness for Teens," a specialized digital therapeutics mobile application designed to address the mental health concerns of teenagers within the Islamic community. The app blends evidence-based psychological interventions with relevant Islamic design and content, offering a holistic mental health support system.